2013
DOI: 10.4000/etnografica.2559
|View full text |Cite
|
Sign up to set email alerts
|

Interurban collective transport and road crashes in Santiago, Cape Verde

Abstract: The text is a facsimile of the print edition. © CRIA etnográfica  fevereiro de 2013  17 (1): [77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95] Interurban collective transport and road crashes in Santiago, Cape Verde Gerard HortaBased on research first begun in Praia (capital of Cape Verde) into the new public organization of its streets and squares -increasingly occupied by cars and other types of motor vehicles -, this article develops a description of the social universe of priva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…Finally, poor health‐related outcomes tied to alcohol use challenge individual and community well‐being (Ferreira‐Borges et al, 2017; Horta, 2013, 2017; Horta & Calvo, 2018), which was our fifth observed value register related to the ongoing experiences of grogue. Heavy drinking cultures, rooted in historical and geopolitical contexts, have emerged in Cabo Verde, with high levels of reported alcohol use and dependence among males (i.e., 10.7%) that far outnumber those of its neighbors (World Health Organization [WHO], 2018, p. 147).…”
Section: Resultsmentioning
confidence: 85%
“…Finally, poor health‐related outcomes tied to alcohol use challenge individual and community well‐being (Ferreira‐Borges et al, 2017; Horta, 2013, 2017; Horta & Calvo, 2018), which was our fifth observed value register related to the ongoing experiences of grogue. Heavy drinking cultures, rooted in historical and geopolitical contexts, have emerged in Cabo Verde, with high levels of reported alcohol use and dependence among males (i.e., 10.7%) that far outnumber those of its neighbors (World Health Organization [WHO], 2018, p. 147).…”
Section: Resultsmentioning
confidence: 85%
“…For urban stations in other African countries, see Barrett 2003;Coulibaly 1993;Hawkins 1958;Jordan 1983;Khayesi 2002;Lopes 2009;Ndiaye andTremblay 2009. 3 Albert 2007;Bähre 2014;Cissokho 2012;Czeglédy 2004;Horta 2013;Jalloh 1998;Jennische 2012;Joshi and Ayee 2002;Khosa 1992;Lewis 1970;Peace 1988;. 4 Clark 1994Grieco, Apt and Turner 1996;Ntewusu 2012;Thiel 2014.…”
Section: Michael Stasikmentioning
confidence: 99%
“…Con dicho concepto se define tanto al vehículo como al tipo de transporte que encarna, abrazando al mismo tiempo su condición de singular y de plural. 2 Para un marco general de esta investigación, véase Horta y Malet Calvo (2014) y Horta (2015): hemos tratado de la accidentalidad en las carreteras (Horta, 2013(Horta, y 2017, de la cotidianidad de la vida colectiva en las estaciones de llegada y salida de los hiace (Malet Calvo, 2011;Horta y Malet Calvo, 2018), de relatos de vida y muerte que se vinculan también en el plano institucional del diseño e implementación de políticas públicas en las vías urbanas e interurbanas (Horta, 2011(Horta, , 2018(Horta, y 2019a, del choque siempre violento entre el anhelo de la formalización estatal de una práctica social colectiva y los procesos cambiantes de autoorganización popular (Horta, 2019b), de las simbolizaciones y las esferas explícitamente expresivas del propio vehículo, de las más groseramente materiales manifestaciones etnográficas de los viajes en hiace... 3 Para un análisis del concepto de movilidad, véase Urry (2007); para una visión panorámica transdisciplinaria, Hannam, Sheller y Urry (2006). A su vez, Glick y Salazar (2013) han introducido consideraciones y matices al paradigma de las "nuevas movilidades", siguiendo el cuestionamiento que postula Franquesa (2011) acerca de la falta de sentido relacional y crítico de dicha escuela.…”
Section: Introductionunclassified